2021
DOI: 10.1186/s12904-021-00820-4
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning preferences in Chinese nursing home residents: results from two cross-sectional studies in Hong Kong and Taiwan

Abstract: Background The proportion of hospital deaths has declined in the past few decades, while the proportions of nursing home deaths have increased. This trend of increasing deaths in long-term care facilities underlines the importance of improving end-of-life care provisions in these settings to meet individual preferences and needs. Under these circumstances, a comprehensive understanding of end-of-life care preferences in local nursing home residents can help healthcare professionals and policyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…This suggested that most of our study participants rarely inquired about ACP and that few healthcare professionals provided relevant information. This finding was consistent with prior studies [9][10][11] which documented that patients with terminal diseases or longterm care residnets were willing to discuss ACP but, in fact, their medical providers rarely discussed this topic with their patients. This might due to the fact that medical personnel were reticent to broach this topic reflecting their concern that early implementation of ACP could engender fear in patients or communicate a sense of hopelessness regarding their prognosis [36].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggested that most of our study participants rarely inquired about ACP and that few healthcare professionals provided relevant information. This finding was consistent with prior studies [9][10][11] which documented that patients with terminal diseases or longterm care residnets were willing to discuss ACP but, in fact, their medical providers rarely discussed this topic with their patients. This might due to the fact that medical personnel were reticent to broach this topic reflecting their concern that early implementation of ACP could engender fear in patients or communicate a sense of hopelessness regarding their prognosis [36].…”
Section: Discussionsupporting
confidence: 90%
“…This percentage was 33.3% in the US [ 8 ], but only 16.1% in Taiwan [ 9 ]. Similarly, studies conducted in Hong Kong found that less than 20% of nursing home residents ( n = 238) ever discussed ACP issues with their family members or healthcare professional [ 10 ] and for seriously ill patients and their caregivers still perceived limited autonomy in ACP decision-making and lack of readiness and awareness of discussion of ACP [ 11 ]. Further, a meta-analysis of 38 studies [ 12 ] found that an average of 33–38% of EOL patients actually received non-beneficial treatment (NBT) during their last 6 months of life.…”
Section: Introductionmentioning
confidence: 99%
“…Social relationships may broaden opportunities for sharing information about ADs and communicating perspectives and preferences about EOL care, which can lead to further discussions and documentation of ACP [ 22 , 24 ]. Although older adults mainly discuss EOL with family members [ 25 , 45 ], in reality, only a few do so because they do not want to burden their family members [ 46 , 47 ]. Furthermore, the number of older Asians living without children or living in single-person households has rapidly increased [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, 79% to 80% of Hong Kong and Taiwanese older adults were reluctant to prolong life in the study scenarios. 15 However, there are little data on the impact of EOL care preferences for older adults in Asia. This article analyzes factors in Taiwan influencing older adults' EOL care preferences and expects to provide evidence in caring for older adults in EOL care.…”
Section: Introductionmentioning
confidence: 99%